Handbook of globalization and the environment - Thai, Khi V., 1941-; Rahm, Dianne; Coggburn, Jerrell D. (Public administration and public policy ;, 2007)
Global environmental standards and performance-based environmental protection have the potential to create efficient corporations, reduce pollution, and protect public interest. The Handbook of Globalization and the Environment examines the local, national, and international impacts of globalization as well as the emerging solutions that support healthy economic growth and environmental protection. This handbook presents global environmental issues and politics, examines environmental management and accountability, and explores global environmental organizations and institutions. It also addre.